A Perceived Significance of Hosting Ata`s Congress in Victoria Falls on Zimbabwe`s Tourism Sector - Zibanai Zhou (Asian Journal of Empirical Research., 2023)
Mega event area associated with urban regeneration, infrastructural development, and legacies in host cities. This study examines economic and social benefits associated with the hosting of ATA congress in Victoria Falls on destination Zimbabwe. Positive and negative effects at micro level are also analysed. Data were collected through 30 self-administered questionnaires on Victoria Falls tourism operators and residents. Results showed that ATA`s congress repositioned Zimbabwe`s tourism sector, endorsed Zimbabwe as a MICE destination, and projected a positive image for the country. Hotels registered high occupancy levels, the municipality`s sewer and water system, and health service facilities were upgraded. On the downside, brothels, taxi fares, vending in undesignated areas and street begging increased.The media ignored these negatives but amplified on the positives. Adoption of a new pricing model for accommodation service providers, equitable distribution of mega events revenue and liberalising the skies to enhance connectivity on destination Zimbabwe are recommended .Keywords: ATA congress, Economic and social significance, Zimbabwe tourism sector.